2016
DOI: 10.5010/jpb.2016.43.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR method for environmental monitoring of approved LM cotton events in Korea

Abstract: The growth area of living modified (LM) cotton has steadily increased every year, since its first commercialization in 1996. Development of environmental risk assessment tools and techniques for LM cotton is required for ecosystem safety. We therefore developed multiplex PCR assays for simultaneous detection of two (MON15985, MON531) and four (GHB614, LLCOTTON25, MON88913 and MON1445) LM cotton events approved in Korea, with event specific primer pairs. The PCR reactions were optimized by using event specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…For high-sensitive detection, large amount of DNA as template is used; however, environmental sample of LMO cannot ensure DNA quality and quantity. Several testing methods released by developers or regulators and several previously reported GMO detection methods recommend that the minimum amount of purified DNA required is 40-100 ng in total reaction volume [6,10,11]. In this study, we detected LMOs using the newly developed multiplex PCR method, which required only 12.5 ng of purified DNA.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For high-sensitive detection, large amount of DNA as template is used; however, environmental sample of LMO cannot ensure DNA quality and quantity. Several testing methods released by developers or regulators and several previously reported GMO detection methods recommend that the minimum amount of purified DNA required is 40-100 ng in total reaction volume [6,10,11]. In this study, we detected LMOs using the newly developed multiplex PCR method, which required only 12.5 ng of purified DNA.…”
Section: Discussionmentioning
confidence: 96%
“…Among the multiplex detection methods for major GM crops, those for cotton have not been well studied because cotton is not a food crop. Multiplex PCR methods have been developed for MON15985, MON531, GHB614, MON88913, LLCOTTON25, and MON1445-2 [10], GHB119 and 281/3006 [17], and GHB119 and T304-40 [3]. In this study, a conventional multiplex PCR method for COT102, MON88701, T304-40, and DAS-81910-7 was newly developed to identify approved GM cotton varieties in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2009, the MOE and National Institute of Ecology (NIE) have been conducting The Environmental LMO Monitoring and Post-Management Project [9,10]. In the project, the natural environmental leakage of LM crops such as cotton, maize, soy bean, and canola was monitored and the risk assessment and management of released LMOs was performed [11][12][13]. A specific LMO detection method is crucial to determine whether the samples collected in this project contain LMOs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a total of 30 LM cotton events including single and stack LMOs were approved in South Korea. A previous study reported LM cotton multiplex detection methods for six events [13]. As approval and unintentional release of LM cotton events have been increasing every year, we needed to develop a new method which can detect almost approved LM cotton events.…”
Section: Introductionmentioning
confidence: 99%